Molecular markers associated with a new source of resistance to the cassava mosaic disease - Lokko, Y.; Danquah, E.Y.; Offei, S.; Dixon, A.; Gedil, Melaku A (2005)
The predominant source of resistance to the cassava mosaic disease (CMD) is known to be polygenic requiring evaluation in multiple environments to characterise resistant genotypes, which makes the detection of genes for resistance using segregation analysis inefficient. Recently, some landraces have been identified which exhibit high levels of resistance to CMD. In this study, molecular markers associated with resistance to CMD in a resistant landrace were identified, using F1 progenies derived from a cross between the CMD resistant landrace TME7 and the susceptible line TMS30555, as a first step in marker assisted breeding for CMD resistance. Bulk segregant analysis (BSA) on the parents, resistant and susceptible DNA pools, using simple sequence repeat (SSR) and amplified fragment length polymorphism (AFLP) markers revealed that an SSR marker, SSRY28-180, donated by the resistant parent was linked with resistance to CMD. Marker-trait association detected by regression analysis showed that the marker, accounted for 57.41% of total phenotypic variation for resistance. The analysis furthershowed that another SSR marker, SSRY106-207 and an AFLP marker, E-ACC/M-CTC-225, accounted for 35.59% and 22.5% of the total phenotypic variation for resistance, respectively. The implication of the results in breeding for resistance to CMD is discussed.